2017
DOI: 10.15376/biores.13.1.569-585
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Potential of Native Fungal Strains of Agave Residues

Abstract: Twelve strains of fungi from residues of Agave durangensis were isolated and identified by molecular techniques for evaluation of their hydrolytic enzyme production capability. A proportion (50%) of the fungal strains belonged to the Aspergillus genus and the other strains used belonged to Alternaria, Neurospora crassa, Mucor sp, Rhizopus sp., Botryosphaeria sp., and Scytalidium sp. The isolated strains were evaluated for their potential to produce extracellular enzymes using different substrates (cellulose, x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…One disk (5 mm diameter, 24 h incubation) per isolated fungus was taken and seeded on agar plates with the medium described by Contreras-Hernández et al [33]. For each strain, two plates of each medium were inoculated with different carbon sources.…”
Section: Screening Of Enzymatic Productionmentioning
confidence: 99%
“…One disk (5 mm diameter, 24 h incubation) per isolated fungus was taken and seeded on agar plates with the medium described by Contreras-Hernández et al [33]. For each strain, two plates of each medium were inoculated with different carbon sources.…”
Section: Screening Of Enzymatic Productionmentioning
confidence: 99%
“…We have also reported that these cellulose nanoplatelets are easier to hydrolyze than larger cellulose, due to their low lignin content, poor crystallinity, and greater surface area [13]. Also, several strains of enzyme-producer fungi have been isolated from Agave species [17,18]. For instance, in earlier studies, we evaluated the enzymatic activity of different fungal strains previously isolated from A. salmiana leaves, with the highest enzymatic activity resulting from a fungus preliminarily classified as belonging to the genus Penicillium (unpublished data).…”
Section: Introductionmentioning
confidence: 99%